Colonial and modern fisheries in the Indian River Lagoon, Florida, USA. (17th June 2019) - Fradkin, Arlene
Abstract: The Indian River Lagoon is a narrow estuary extending 251 km (156 mi) along the Atlantic coast of Florida. One of the most biodiverse waterways in North America, this aquatic ecosystem is currently home to more than 4, 000 plant and animal species, including approximately 700 fish species. According to archaeological faunal evidence from a mid‐18th‐century colonial settlement in the northern Indian River Lagoon region, this estuary also provided an abundance of wild animal resources in the past. The colonists relied heavily upon the lagoon as indicated by the predominance of ray‐finned fishes in the examined faunal samples. A comparison between particular fish species represented in the archaeological colonial record and those currently found in the lagoon today demonstrates that these fishes were comparable in relative frequency and size.